Changes of B2B promotion in the Czech Republic - Jaderná, Eva; Mlázovský, Martin; Tomašík, Marek (Univerzita Palackého v Olomouci, 2019)
The paper aims to describe the evolution during last decade and current state of the B2B marketing in the Czech Republic. Data by B2B monitor were analyzed and interpreted to identify the trends in the B2B marketing. The paper shows the tendency to save money in the context of B2B marketing activities. New trends in an application of B2B marketing tools are presented. The study is completed by an interesting view of an expert in the B2B marketing. A deep interview with an expert has confirmed data by B2B monitor and discovered other problems in the B2B marketing at present.
Změny B2B promotion v České republice
Keywords: B2B marketing; B2B monitor; B2B promotion; events; marketing budget; B2B marketing; B2B monitor; B2B promotion; eventy; marketingový rozpočet